1999
DOI: 10.1002/(sici)1097-0347(199910)21:7<627::aid-hed7>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MMPS, MT‐MMP, and TIMPs in squamous cell carcinoma of the oral cavity: Correlations with tumor invasion and metastasis

Abstract: Background. Matrix metalloproteinases (MMPs) that degrade the extracellular matrices (ECMs) have been thought to play an important role in both the invasion and metastasis of tumors. However, the detailed role of MMPs and TIMPs (tissue inhibitors of MMP) on the biological behavior of tumor cells has yet to be elucidated in vivo. The aim of the present study was thus to determine whether expression of MMPs on tumor cells is associated with such clinicopathological features as the invasive and metastatic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
155
0
10

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(175 citation statements)
references
References 0 publications
10
155
0
10
Order By: Relevance
“…These enzymes are capable of cleaving most ECM components, as well as other biologically important proteins such as growth factors, other proteases, adhesion molecules, and cell surface receptors (Table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] With a widening understanding of MMP substrates, a more complex role for these enzymes in tumor growth and metastasis has been appreciated.…”
Section: Matrix Metalloproteasesmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes are capable of cleaving most ECM components, as well as other biologically important proteins such as growth factors, other proteases, adhesion molecules, and cell surface receptors (Table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] With a widening understanding of MMP substrates, a more complex role for these enzymes in tumor growth and metastasis has been appreciated.…”
Section: Matrix Metalloproteasesmentioning
confidence: 99%
“…Although most studies evaluate only one or two MMPs within a given head and neck site, studies have examined expression of multiple TIMPs and MMPs in oral cavity SCC. 12,22 Interestingly, these studies commonly identify upregulation of TIMP-1, which is associated with a poor survival. Levels of TIMP-2 are often unchanged between tumors and adjacent normal specimens.…”
Section: Assessment Of Matrix Metalloproteases In Head and Neck Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…22 Some studies have suggested an association between gelatinase mRNA, immunoreactive protein or enzyme activity with invasion or lymph node metastasis in some tumor types according to their malignancy category. [23][24][25] However, the data relating to the significance of circulating MMP-9 in patients with HNSCC as a prognostic marker have been less studied. The present study was conducted to measure preoperative or pretreatment serum MMP-9 levels in patients with head and neck squamous cell carcinoma and to correlate them with clinical behavior and disease outcome as well as to study whether the circulating MMP-9 levels would correlate to MMP-9 immunohistochemical staining in the corresponding primary tumor or to the tumor burden.…”
mentioning
confidence: 99%
“…The expression of MMPs in head and neck cancers has been reported. [4][5][6][7][8][9][10][11][12][13][14] Those studies demonstrated that immunoreactive MMP-2 and MMP-9 staining was stronger in patients with lymph node metastasis and was associated with lower survival rates. [11][12][13][14] MMP-7 is one of the few MMPs overexpressed by carcinoma cells rather than by stromal cells.…”
mentioning
confidence: 99%